Novel drug - dinutuximab for high-risk neuroblastoma - Supriya Kushwah; Ashutosh Kumar; S Shabnam (Apollo Medicine)
Neuroblastoma is the most common extracranial tumor in children aged <5 years. Prognosis of high-risk neuroblastoma is not good even after use of aggressive chemotherapy. Newer drug anti-GD2 monoclonal antibodies, dinutuximab in combination with granulocyte-macrophage colony-stimulating factor or interleukin-2, have been recently approved by Food and Drug Administration for the treatment of high-risk neuroblastoma. Dinutuximab binds to the glycolipid GD2 present on neuroblastoma cells and cells of neuroectodermal origin and enhances cell lysis through antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity.